1996
DOI: 10.1182/blood.v87.1.102.bloodjournal871102
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of the basic helix-loop-helix transcription factor SCL on erythroid and monocytic differentiation

Abstract: The SCL gene (also called Tal-1 or TCL5) was identified because of its association with chromosomal translocations in childhood T-cell lymphoid leukemias. SCL codes for a basic helix-loop-helix (bHLH) factor that can function as a transcriptional activator or repressor. In the adult, SCL expression is restricted to hematopoietic cells and tissues, but its function in the process of lineage commitment is unknown. The present study was designed to address the role of SCL in hematopoietic cell differentiation. SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 1 publication
0
24
0
Order By: Relevance
“…Through unbiased mass spectrometry analysis, we identify here these proteins as components of the core TAL‐1 complex, in which TAL‐1 acts as a nucleation platform (Lecuyer et al , 2002). In this complex, TAL‐1 is limiting since elevating TAL‐1 dosage in the cell increases GPA expression (Hoang et al , 1996), while E2A is not, as shown here for E12. Given that E2A is partitioned in TAL‐1 and non‐TAL‐1 complexes, these observations are not surprising.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Through unbiased mass spectrometry analysis, we identify here these proteins as components of the core TAL‐1 complex, in which TAL‐1 acts as a nucleation platform (Lecuyer et al , 2002). In this complex, TAL‐1 is limiting since elevating TAL‐1 dosage in the cell increases GPA expression (Hoang et al , 1996), while E2A is not, as shown here for E12. Given that E2A is partitioned in TAL‐1 and non‐TAL‐1 complexes, these observations are not surprising.…”
Section: Discussionmentioning
confidence: 77%
“…NIH 3T3, TF‐1, UT‐7 and MEL cells were cultured and stimulated to differentiate as described previously (Hoang et al , 1996; Lahlil et al , 2004). Human CD34 + cells were purified and differentiated as described (Freyssinier et al , 1999; Ravet et al , 2004).…”
Section: Methodsmentioning
confidence: 99%
“…This consideration suggests that the availability of regulators that can drive cells to other fates is a necessary side‐effect of the initial growth factor requirements of T‐cell precursors, before they can switch over to TCR dependence. Correct regulation of the levels of these regulators is probably vital to channel their activities correctly; PU.1 and SCL effects, and Id2 effects by their nature, are dose dependent (76, 80–83). Whether or not the levels expressed in early T‐cell precursors account for the lineage plasticity observed in these populations is discussed later.…”
Section: Functions That Can Maintain Plasticity: Evidence From Gene Ementioning
confidence: 99%
“…TF-l cells have been derived from a patient with erythroleukemia (Kitamura et al, 1989) and express high levels of an abnormal truncated EpoR (Winkelmann et al, 1995). The growth of these cells is dependent on the presence of granulocyte-macrophage colony stimulating factor (GM-CSF) or interleukin (IL)-3, while they proliferate only transiently in response to Epo which induces an erythroid differentiation program after 1 week of culture (Hoang et al, 1996).…”
Section: Introductionmentioning
confidence: 99%